Land drainage development processes and changes in the context of runoff change in northern Lithuania - Stankevičienė, Rasa; Survilė, Oksana (International Conference “Environmental Engineering”, 2020)
The impact of the drainage of excessively wet land on river runoff has so far been assessed differently and very carefully because of its complexity and diversity. The article analyses changes of drained land areas and runoff in the river basins of Mūša, Lėvuo Tatula and Nemunėlis. Wet land areas in the Mūša, Lėvuo and Nemunėlis rivers basins account for more than 70% from the total basins area and in the Tatula about 90%. Increase of drained land areas in the studied river basins has no significant influence on the change of river runoff. Studies have shown that the change in drained land areas did not affect the change in runoff height. Drainage does not have a significant effect on changes in the annual runoff distribution of the studied rivers.
Keywords: draining; land drainage; river runoff; wetland